Codelivery of salinomycin and chloroquine by liposomes enables synergistic antitumor activity in vitro. (July 2016) - Xie, Fangyuan; Zhang, Siyue; Liu, Junjie; Gong, Zhirong; Yang, Kaixuan; Zhang, He; Lu, Ying; Zou, Hao; Yu, Yuan; Chen, Yan; Sun, Zhiguo; Wang, Xinxia; et al.
Aim: To improve the suboptimal therapeutic efficacy of salinomycin (SAL) toward liver cancer cells using chloroquine (CQ) combination by the liposomes co-delivering SAL and CQ (SCNL).Materials & methods: The synergy of these two drugs was evaluated in liver cancer cells (HepG2) and liver cancer stem cells (LCSCs) by median-effect analysis. SCNL with optimized ratio were developed. The cytotoxic effect and basal autophagy flux (measure of autophagic degradation activity) of various formulations were evaluated.Results & conclusion: CQ could significantly increase the cytotoxic effect of SAL in HepG2 cells, but not in HepG2-LCSCs, due to the greater basal autophagy flux in HepG2 cells. This combination therapy is promising for liver cancer treatment by eradicating liver cancer cells and LCSCs.